2004
DOI: 10.1073/pnas.0401557101
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide facilitates cardiomyogenesis in mouse embryonic stem cells

Abstract: Stem cell therapy holds great promise for the replacement of damaged or dysfunctional myocardium. Nitric oxide (NO) has been shown to promote embryonic stem (ES) cell differentiation in other systems. We hypothesized that NO, through NO synthase gene transfer or exogenous NO exposure, would promote the differentiation of mouse ES cells into cardiomyocytes (CM). In our study, NO treatment increased both the number and the size of beating foci in embryoid body (EB) outgrowths. Within 2 weeks, 69% of the inducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
103
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(110 citation statements)
references
References 21 publications
3
103
1
Order By: Relevance
“…Nitric oxide (NO), a key vertebrate signaling molecule, has been previously shown to enhance cardiomyocyte generation from mouse ES cells via a mechanism, which may involve altered redox states [33]. Addition of a NO adduct (diethylenetriamine-NO), however, did not induce beating foci appearance in our experimental model (results not shown).…”
Section: Resultsmentioning
confidence: 62%
“…Nitric oxide (NO), a key vertebrate signaling molecule, has been previously shown to enhance cardiomyocyte generation from mouse ES cells via a mechanism, which may involve altered redox states [33]. Addition of a NO adduct (diethylenetriamine-NO), however, did not induce beating foci appearance in our experimental model (results not shown).…”
Section: Resultsmentioning
confidence: 62%
“…Beside ROS, other signaling molecules have also been implicated in the regulation of cardiac differentiation. A recent article suggests a dose-dependent effect of nitric oxide, with low doses being permissive for differentiation and higher doses leading to apoptosis (Kanno et al, 2004).Here, we report that in vivo NOX4 mRNA is localized in the early embryonic mouse heart within cardiac cells, as revealed by in situ hybridization coupled with immunofluorescence identification of cardiac markers. Because NOX4 is the main NOX isoform expressed in mouse ESC and its down-regulation by different RNAi methods impairs ESC differentiation into cardiomyocytes, we propose that NOX4-dependent ROS production is critical for cardiogenesis.…”
mentioning
confidence: 75%
“…Beside ROS, other signaling molecules have also been implicated in the regulation of cardiac differentiation. A recent article suggests a dose-dependent effect of nitric oxide, with low doses being permissive for differentiation and higher doses leading to apoptosis (Kanno et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with NOS-1, NOS-2, and NOS-3 mRNA and protein levels were also induced during ES cell differentiation (18,19), thereby demonstrating the involvement of NO signaling components during differentiation of ES cells into cardiac cells. Previous studies by other investigators (20) have shown increased cardiomyogenesis with NO donors and by delivery of the NOS-2 gene in mouse ES cells.…”
mentioning
confidence: 99%